Thematic Development Trends in Government Bureaucracy Research: A Bibliometric Analysis Based on Global Databases - M. Rafi; Muchid Albintani; Ardiansyah Ardiansyah; Al Fauzi Rahmat; Alam Mahadika (Government & Resilience, 2026)
The gap and limited global references in interpreting government bureaucracy (GB) studies have underpinned the urgency of this study. The purpose of this study is to identify thematic development trends in articles on government bureaucracy (GB). Through bibliometric analysis using the R Studio package Biblioshiny, this literature review examines articles on GB from 2016 to 2025. Using data from 109 journal articles retrieved from the Scopus database and focusing on subject trends, co-occurrence, thematic evolution, and international collaboration networks. The results of the study indicate that the development of government bureaucracy (GB) research themes reflects the changing circumstances that initially were mostly conducted at the national and international government levels, continuing to spread to local governments with the main subject keywords including bureaucracy, corruption, government bureaucracy, international development, and local government as rapidly growing topics in the study of GB. In addition, this study still has limitations because it only examines English-language publications from the last ten years on social science subjects and Scopus databases. The researcher recommends a more comprehensive data coverage, scope, and various other languages to emphasize the need for increased attention to the study of GB.